1961
DOI: 10.1037/h0041511
|View full text |Cite
|
Sign up to set email alerts
|

Studies of distributed practice: XX. Sources of interference associated with differences in learning and retention.

Abstract: The present studies deal with learning and retention of pairedassociate lists as a function of massed and distributed acquisition. As interlist interference builds up across lists, distributed practice is more and more likely to facilitate paired-associate learning; this fact is quite clear if learning is carried to a fairly high level (Underwood & Richardson, 1958). However, there is no indication that for varying levels of interlist interference distributed practice will be followed by appreciably better ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

1961
1961
1976
1976

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…While the opposite relationship is more likely correct, the matter can be resolved directly. Both in an earlier study (Underwood & Schulz, 1961), and in the present one, the number of trials to attain a common criterion did not differ as a function of stage of practice and still PI increased directly as a function of number of prior lists learned.…”
Section: Discussioncontrasting
confidence: 44%
“…While the opposite relationship is more likely correct, the matter can be resolved directly. Both in an earlier study (Underwood & Schulz, 1961), and in the present one, the number of trials to attain a common criterion did not differ as a function of stage of practice and still PI increased directly as a function of number of prior lists learned.…”
Section: Discussioncontrasting
confidence: 44%
“…A similar repeated-extinction hypothesis has been suggested as a possible explanation for superior retention following acquisition under distributed rather than massed practice. In interpreting such a finding obtained under a similarstimulus-changed-response design, Underwood and Schulz (1961) suggested that:…”
Section: Discussionmentioning
confidence: 99%
“…The last report in this series (Underwood & Schulz, 1961) indicated that when distributed practice facilitates acquisition of paired-associate lists it does so as a consequence of interference occurring during the responseintegration phase of learning. The interference was produced by having 5s learn lists containing elements which subsequently interfered with the response learning of the critical or test list.…”
mentioning
confidence: 93%